Specificity of HTLV screening tests and its impact on health care program costs: The perspective of antenatal screening in Brazil - Rosadas, Carolina (Rev Soc Bras Med Trop, 2021)
INTRODUCTION: Brazil ranks first in the number of HTLV-1/-2-infected individuals worldwide. The high morbidity and mortality of HTLV-1-associated diseases, especially following infection in infancy, requires strong action to reduce vertical transmission. METHODS: To facilitate the appraisal of the implementation of the HTLV antenatal screening program by the Brazilian Ministry of Health, we determined the costs in distinct scenarios according to HTLV seroprevalence, specificity of the screening test, and type of confirmatory test. RESULTS: HTLV antenatal screening would cost R$ 55,777,012-R$ 77,082,123/year. Screening assays with high specificity reduce the need and cost of confirmatory assays by up to 25%. CONCLUSIONS: Careful selection of the screening assay is required to optimize the program.